GENDER METAPHOR: A COMPARATIVE ANALYSIS OF MALE AND FEMALE POETS - Simorangkir, Raslima; Wulandari, Vanny; Dalimunte, Vina Fitriani; Putri, Riska Ananda; Rangkuti, Rahmadsyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2024)
This research conducts a comparative analysis of the metaphors used in Alfred Lord Tennyson's poem